Mechanisms of Chronotropic Incompetence in Heart Failure With Preserved Ejection Fraction. (March 2020) - Sarma, Satyam; Stoller, Douglas; Hendrix, Joseph; Howden, Erin; Lawley, Justin; Livingston, Sheryl; Adams-Huet, Beverley; Holmes, Courtney; Goldstein, David S.; Levine, Benjamin D.
Abstract : Background: Chronotropic incompetence is common in heart failure with preserved ejection fraction (HFpEF) and is associated with impaired aerobic capacity. We investigated the integrity of cardiac β–receptor responsiveness, an important mechanism involved in exertional increases in HR, in HFpEF and control subjects. Methods: Thirteen carefully screened patients with HFpEF and 13 senior controls underwent exercise testing and graded isoproterenol infusion to quantify cardiac β–receptor–mediated HR responses. To limit autonomic neural influences on heart rate (HR) during isoproterenol, dexmedetomidine and glycopyrrolate were given. Isoproterenol doses were increased incrementally until HR increased by 30 beats per minute. Plasma levels of isoproterenol at each increment were measured by liquid chromatography with electrochemical detection and plotted against HR. Results: Peak VO2 and HR (117±15 versus 156±15 beats per minute; P <0.001) were lower in HFpEF than senior controls. Cardiac β–receptor sensitivity was lower in HFpEF compared to controls (0.156±0.133 versus 0.254±0.166 beats per minute/[isoproterenol ng/mL]; P <0.001). Seven of 13 HFpEF subjects had β-receptor sensitivity similar to senior controls but still had lower peak HRs (122±14 versus 156±15 beats per minute; P <0.001). Conclusions: Contrary to our hypothesis, patients with HFpEF displayed impaired cardiac β–receptor sensitivity compared with senior controls. In the 7 out of 13 patients with HFpEF with age-appropriate β–receptor sensitivity, peak HR remained low, suggesting impaired sinus node β-receptor function may not fully account for low exercise HR response. Rather in some patients with HFpEF, chronotropic incompetence might reflect premature cessation of exercise before maximal sinus node activation. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02524145. Abstract : Supplemental Digital Content is available in the text.